New Roles for MicroRNAs in Old Worms - Elder, Corrina R.; Pasquinelli, Amy E. (Frontiers in Aging, 2022)
The use of Caenorhabditis elegans as a model organism in aging research has been integral to our understanding of genes and pathways involved in this process. Several well-conserved signaling pathways that respond to insulin signaling, diet, and assaults to proteostasis have defined roles in controlling lifespan. New evidence shows that microRNAs (miRNAs) play prominent roles in regulating these pathways. In some cases, key aging-related genes have been established as direct targets of specific miRNAs. However, the precise functions of other miRNAs and their protein cofactors in promoting or antagonizing longevity still need to be determined. Here, we highlight recently uncovered roles of miRNAs in common aging pathways, as well as new techniques for the ongoing discovery of miRNA functions in aging C. elegans.